2021
DOI: 10.1182/blood.2020006675
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 signaling controls dendritic cell location and activation at steady state and in inflammation

Abstract: Dendritic cells (DCs) encompass several cell subsets that collaborate to initiate and regulate immune responses. Proper DC localization determines their function and requires the tightly controlled action of chemokine receptors. All DC subsets express CXCR4, but the genuine contribution of this receptor to their biology has been overlooked. We addressed this question using natural CXCR4 mutants resistant to CXCL12-induced desensitization and harboring a gain of function that cause the warts, hypogammaglobuline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 79 publications
2
17
1
Order By: Relevance
“…Histology assessment confirmed marked skin inflammation, with increased epidermis and dermis thickness (Figure 5a,b). DC subsets were identified (Figure 5c) and their analysis showed that dysplasia-associated inflammation was driving MHC II level diminution in LCs and skin DC subsets (Supplemental Figure S4a), as expected [33,40]. As for GILZ expression, we first confirmed that LCs and cDC2 expressed the highest GILZ levels among skin DCs in the FVB/N background (Figure 5d and Supplemental Figure S4b, DC subsets from WT mice), as in the C57BL/6J background (Figure 1).…”
Section: Gilz Expression Is Maintained In Skin and Sdln DC Subsets In The Context Of Chronic Inflammationsupporting
confidence: 71%
See 4 more Smart Citations
“…Histology assessment confirmed marked skin inflammation, with increased epidermis and dermis thickness (Figure 5a,b). DC subsets were identified (Figure 5c) and their analysis showed that dysplasia-associated inflammation was driving MHC II level diminution in LCs and skin DC subsets (Supplemental Figure S4a), as expected [33,40]. As for GILZ expression, we first confirmed that LCs and cDC2 expressed the highest GILZ levels among skin DCs in the FVB/N background (Figure 5d and Supplemental Figure S4b, DC subsets from WT mice), as in the C57BL/6J background (Figure 1).…”
Section: Gilz Expression Is Maintained In Skin and Sdln DC Subsets In The Context Of Chronic Inflammationsupporting
confidence: 71%
“…For skin cell isolation, tissue pieces were dissected from mouse ear or from depilated (Veet Cream for sensitive skin, used post-mortem) mouse belly and flanks, and processed as previously described [33,36]. Briefly, tissue pieces were incubated for 90 min in dispase (2.5 U/mL, Gibco BRL) at 37 • C. The epidermis and dermis were then separated and cut into small pieces and further incubated for 1 h in a solution of collagenase D (1 mg/mL, Roche) and DNase I (12.5 U/mL, Roche) at 37 • C. Tissue dissociation was then completed using 18-G syringes and samples were further incubated for 15 min at 37 • C before filtration through 70-µm cell strainers.…”
Section: Mouse Sample Processingmentioning
confidence: 99%
See 3 more Smart Citations